Experimental study on effect of loading rate on mechanical properties of CFRP equipment cabin skeleton laminates. (October 2019) - Wang, Yongyan; Feng, Xuezhi; Zhang, Xiangfeng; Liu, Yaqi; Wang, Hao
Abstract: With the development of high-speed train technology, the dynamic problems caused by track irregularity and the stress maximization of CFRP equipment cabin skeleton at the edge of the beam are becoming increasingly prominent. In this paper, the tensile and compressive properties of carbon fiber laminates under different loading rates are studied by means of universal material mechanics experimental machine. The curves of tensile and compressive strength under different loading rates are obtained. The variation trends of tensile and compressive stiffness are analysed and the failure modes are summarized. It is found that the tensile strength of carbon fiber laminates does not change with the change of loading rate, but the compressive strength increases with the increase of loading rate in the range of 0 mm/min-6 mm/min and considering the influence of certain error. When the load is less than 30kN, the tensile stiffness of the material is not affected by loading rate. As the loading rate increases, the stiffness and compression stiffness increase.